Pemanfaatan YouTube “Easy German” dalam Meningkatkan Keterampilan Menulis Mahasiswa Bahasa Jerman Universitas Pattimura - Melani Sahetapi; Juliaans E R Marantika; Carolina Lestuny (Universitas Pattimura, 2026)
This study aims to analyze the effect of using the YouTube channel “Easy German” on the writing performance of students in the German Language Education Program at Pattimura University. The research method employed was a quantitative approach using a one-group pretest-posttest design. The research sample consisted of students in the German Language Education Program, Class of 2024. The data collection technique used to measure students’ writing skills was a writing skills test: pre-test and post-test. The data obtained were analyzed using a paired sample t-test. The results of the study indicate a significant improvement in students’ writing skills following the implementation of video-based learning from the YouTube channel Easy German. These results prove that the use of the YouTube channel “Easy German” has a positive and effective impact on improving students’ German writing skills. This medium provides authentic language exposure, thereby helping students develop ideas, enrich their vocabulary, and understand grammar in context.